Molecular Bird Sexing of Tanimbar Cockatoos (Cacatua goffiniana) by Using Polymerase Chain Reaction Method - Ratu Fresa Khoirotunnisa Hidayat; Diana Savitri; Irhamna Putri; Warih Pulung Nugrahani; Aris Haryanto (Universitas Gadjah Mada, 2021)
This study aimed to determine the sex of Tanimbar Cockatoo (Cacatua goffiniana) birds by amplifying Chromodomain Helicase DNA-binding-1 (CHD-1) gene on Z and W sex chromosomes as well as to compare the quality of DNA extraction and PCR amplification products from samples derived from peripheral blood and plucked feathers. This work used five C. goffiniana birds which were collected from the Wildlife Rescue Center (WRC) in Pengasih, Kulon Progo, Yogyakarta. From each C. goffiniana, feather samples were collected by plucking feathers on the ventral wing and peripheral blood samples were taken by cutting their nails and collecting the blood into microhematocrit tubes containing heparin. The next stage was DNA extraction and DNA amplification on the CHD-1 gene using the PCR method by NP, P2, and MP primer pairs. Then, products of DNA extraction and PCR amplification were electrophoresed on 1.5% agarose gel and visualized under a UV light transilluminator with a wavelength of 260 nm. The visualization showed that samples from peripheral blood generated clearer DNA fragments compared to plucked feathers. Two of the five samples were male C. goffiniana and the other three samples were females. In the male Tanimbar Cockatoo was amplified a single DNA fragment of the Z sex chromosome in size of 300 bp, whereas in the female C. goffiniana was amplified double DNA fragments of Z and W sex chromosomes in size of 300 bp and 400 bp respectively. The DNA quality showed that the DNA quality from peripheral blood samples were better in quality than the DNA collected from plucked feather samples.